Abdominal pain developing from a polyarteritis nodosa-induced hepatic aneurysm - Özgül Yiğit; Meltem Erol; Ömer Faruk Beşer; Ramazan Albayrak; Hüseyin Kaya; Mehmet Toksöz; Özgür Kasapçopur (Turkish Journal of Gastroenterology, 2019)
-